English immigration discourse in the scientific paradigm of critical research: review of the monograph by M.S. Matytsina - I. V. Chekulai (Дискурс профессиональной коммуникации, 2020)
The reviewed work is the monograph written by M.S. Matytsina, the Associate Professor of Foreign Languages Department, Lipetsk State Technical University. In the book the author describes the development trends of the English immigration discourse in the scientific paradigm of critical research. The author focuses on establishing the relationship between discourse and society, and the connecting link in this interaction is cognitive structures, which are a subjective mental construct of participants in the communicative situation. The aim of the study is to analyze and systematize the existing knowledge about the problem of immigration in dynamically developing societies of Great Britain and the USA, assess the state of development of language processes that occur as a result of observed trends, and also identify the place and role of the language content of the discourse in social relations building. The study broadens and deepens the existing knowledge about various techniques of modern political rhetoric and discursive phenomena. The monograph is addressed to specialists in the field of discursive analysis, language theory, political linguistics, doctoral students, graduate students, applicants, teachers and students of institutes and departments of foreign languages.